A case of Scalp Rosacea treated with low dose doxycycline and probiotic therapy and literature review on therapeutic options. Issue 4 (17th April 2016) - Fortuna, M. C.; Garelli, V.; Pranteda, G.; Romaniello, F.; Cardone, M.; Carlesimo, M.; Rossi, A.
Abstract: Rosacea is a common chronic inflammatory disorder showing a wide range of clinical features such as telangiectasia, erythema, papules, and pustules primarily involving the central part of face (forehead, cheeks and nose) although extra facial manifestation have been described. We describe a case of rosacea with predominant scalp involvement successfully treated with a 8‐week‐course of doxycycline 40 mg once a day and probiotic therapy twice a day (Bifidobacterium breve BR03, Lactobacillus salivarius LS01 1 × 10 9 UFC/dose).